2015
DOI: 10.1371/journal.pone.0121705
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risks of Mortality and Atherosclerotic Complications in Incident Hemodialysis Patients Subsequently with Bone Fractures: A Nationwide Case-Matched Cohort Study

Abstract: BackgroundHemodialysis (HD) patients with bone fractures have an increased risk for death. However, the risks for mortality and atherosclerotic complications in incident HD patients subsequently with bone fractures are unknown.MethodsData derived from the Taiwan National Health Institute Research Database between January 1997 and December 2008 was analyzed. The enrolled patients included 3,008 incident HD patients subsequently with a single long bone fracture (LB Fx) and 2,070 incident HD patients subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Finally, one study reported that people with fractures had a similar chance to develop PVD in one study (HR ¼ 1.06; 95% CI, 0.91 to 1.23, p ¼ 0.44). (34)…”
Section: Site Of Fractures and Cvdmentioning
confidence: 99%
“…Finally, one study reported that people with fractures had a similar chance to develop PVD in one study (HR ¼ 1.06; 95% CI, 0.91 to 1.23, p ¼ 0.44). (34)…”
Section: Site Of Fractures and Cvdmentioning
confidence: 99%
“…Several studies report that nondialysis patients aged over 50 with estimated glomerular filtration rate (eGFR) below 60 mL/min/1.73 m 2 also have a twofold greater risk for hip fractures than individuals without CKD [37]. A hip fracture critically limits activities of daily living and increases fracture-related mortality [810], and this trend is more evident in dialysis patients [11, 12]. Japanese dialysis patients, however, have relatively better prognosis with regard to survival after a hip fracture [13].…”
Section: Introductionmentioning
confidence: 99%
“…The main complication of ROD is represented by fractures, which is a risk factor for mortality in dialysis patients [ 36 , 37 ]. In this study, there was no evidence that ROD was a prognostic factor in HD patients.…”
Section: Discussionmentioning
confidence: 99%